2006
DOI: 10.1097/01.brs.0000201331.50597.ea
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the SRS-22 Health-Related Quality of Life Questionnaire Function Domain

Abstract: With a minor revision of question 18 (related to going out) the internal consistency of the SRS-22 Function domain has been improved in idiopathic scoliosis patients < 18 years of age. Deletion of question 15 (related to financial considerations) has a variable, small effect depending on patient group. Retention of question 15 is recommended unless a cultural variable, such as differences in healthcare payment schemes, substantially lowers domain psychometric properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(148 citation statements)
references
References 17 publications
1
145
0
2
Order By: Relevance
“…The sample is heterogeneous for age, with both adolescents and adults included. Nevertheless, the version of the questionnaire used has shown similar validity for the age range (10-40 years) included in the analysis [5,7].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The sample is heterogeneous for age, with both adolescents and adults included. Nevertheless, the version of the questionnaire used has shown similar validity for the age range (10-40 years) included in the analysis [5,7].…”
Section: Discussionmentioning
confidence: 98%
“…The total score was presented in three ways: the raw sum score without satisfaction (possible range 20-100), the average sum score (raw score/20), and the raw score percentage of improvement. The questionnaire used was the revised version, which includes the modification of question 18 [5,7].…”
Section: Srs-22 Patient Questionnairementioning
confidence: 99%
“…The cosmesis of the back and shoulders is of great importance to the adolescents with idiopathic scoliosis and their family [1,2,10,19,21]. Raso et al [19] showed that the shoulder balance plays an important role in the cosmesis of AIS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with non-idiopathic scoliosis, leg-length discrepancy, pelvis tilt or hip flexion deformity were excluded from the study. The average age was 14.3 years (range [11][12][13][14][15][16][17], the average Risser signs was 2.8 (range [1][2][3][4][5]. The average main thoracic curve was 53.0°(range 40°-89°), and the average proximal thoracic curve was 44.3°(range 34°-65°) ( Table 1).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation